1999
DOI: 10.1080/00071669987160
|View full text |Cite
|
Sign up to set email alerts
|

Early T-maze behaviour and subsequent growth in commercial broiler flocks

Abstract: Two batches of 2000 mixed-sex broiler chicks were obtained, one in summer and one in winter. Each flock was housed on the floor at a commercial farm. At 2 or 3 d of age, the latencies to escape from a T-maze were measured in 1044 and 1180 chicks in the summer and winter flocks, respectively. Chicks were assigned to high (HP), moderate (MP) or low (LP) performance categories if their escape latencies were below 40 s, between 40 to 90 s, or above 90 s, respectively. Ninety male and 90 female chicks from each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…It is possible that the small effect (HP 2.3% heavier than LP at 8 wk; P < 0.02) of sociality on growth reported by Marin et al (2003) is masked in feed-restricted settings, where other factors become determining of individual growth rate differences, or that the cost of increased social interactions outweighs the stress-reducing effects in HP individuals. It is further possible that the difference between the results of Marin et al (1999Marin et al ( , 2003 and our findings is influenced by the main stressors experienced by the birds. Although the stress of living in a large-scale flock may be 1 of the major stressors in the life of an ad libitum-fed broiler, feed restriction can be expected to be the main cause of stress in broiler breeders, and although social support can successfully buffer social stress in the first case, it is probably much less effective at alleviating restriction-induced stress (Rault, 2012).…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…It is possible that the small effect (HP 2.3% heavier than LP at 8 wk; P < 0.02) of sociality on growth reported by Marin et al (2003) is masked in feed-restricted settings, where other factors become determining of individual growth rate differences, or that the cost of increased social interactions outweighs the stress-reducing effects in HP individuals. It is further possible that the difference between the results of Marin et al (1999Marin et al ( , 2003 and our findings is influenced by the main stressors experienced by the birds. Although the stress of living in a large-scale flock may be 1 of the major stressors in the life of an ad libitum-fed broiler, feed restriction can be expected to be the main cause of stress in broiler breeders, and although social support can successfully buffer social stress in the first case, it is probably much less effective at alleviating restriction-induced stress (Rault, 2012).…”
Section: Discussionmentioning
confidence: 42%
“…It was hypothesized previously that highly social and less fearful animals experience a better welfare situation in large-scale flocks, with improved growth as less energy is directed toward stress and fear responses (Kikusui et al, 2006;Siegel et al, 2008). Comparing the performance of individual chicks in a sociality T-maze at just 2 to 3 d, Marin et al (1999Marin et al ( , 2003 found a positive correlation between early social behavior and later slaughter weight that was reproduced over a range of environments. In our study, T-maze performance at 2 d showed no correlation with growth at any age or with performance in the same maze at 3 wk of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations